Common ion effect enhanced cobalt hexacyanoferrate for aqueous Na-ion battery. (November 2022) - Xiang, Bingnan; Zhang, Junwei; Zhang, Xikun; Yan, Weibin; Xu, Jiaxi; Wang, Junlong; Yu, Haoxiang; Yan, Lei; Zhang, Liyuan; Shu, Jie
Abstract: Given the merits of rich reserves, high ion conductivity and non-combustion property, aqueous sodium ion batteries (SIBs) were once considered as high-quality substitutes for organic lithium ion batteries. However, due to the large radius of carrier sodium ion and unstable structure of electrode materials, the practical implementation of aqueous SIBs is seriously impeded. In this work, a reliable aqueous SIB is constructed by employing Na2 Co[Fe(CN)6 ] as cathode, which is synthesized by co-precipitation assisted electrochemical synthesis. As a Prussian blue analogue (PBA), Na2 Co[Fe(CN)6 ] inherits open framework structure, ion insertion stability and electrochemical tunability. Benefitting from common ion effect, Na2 Co[Fe(CN)6 ] can maintain stable host structure in the SIBs with CoSO4 as an additive of electrolyte, and exhibits an exceptional cycling stability without capacity decay over 2000 cycles and outstanding rate performance. By further exploring the changes in crystal structure, elemental valence states and ion storage kinetics, it fully explains the structural and electrochemical stability of Na2 Co[Fe(CN)6 ] as the cathode for aqueous SIBs and the mechanism of Na + insertion/extraction during cycling process. This work provides a pathway to settle the problems of large carrier ion and structural instability in aqueous SIBs, and greatly broadens the path of its research and development. Graphical abstract: Image 1 Highlights: Na2 Co[Fe(CN)6 ] is synthesized by electrochemical assisted co-precipitation. Common ion effect enhances the electrochemical property of sodium ion battery. The capacity retention is as high as 100% over 2000 cycles at 1000 mA g −1 . The Na  +  storage mechanism is related to the bimetallic redox reaction.